2013
DOI: 10.1242/jcs.109777
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative kinetics analysis of BMP2 uptake into cells and its modulation by BMP antagonists

Abstract: SummaryBone morphogenetic proteins (BMPs) are members of the TGFb family of signaling proteins and play an important role during development and in tissue formation. BMP signaling is a well-studied process, which is initiated through binding of cognate receptors and processed through activation of Smad downstream mediators. A hallmark of BMP signaling is its modulation at the extracellular level through specific antagonists. Although it had been shown that BMP and TGFb receptors are internalized following acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 35 publications
4
41
2
Order By: Relevance
“…The association of dynamin with the clathrin‐dependent pathway is well known, though some evidence also implicates its association with the caveolin‐dependent pathway (Doherty & McMahon, ). These results are consistent with the previous studies showing that chlorpromazine and dynasore reduced rhBMP‐2 internalization (Alborzinia et al, ; Jortikka, Laitinen, Lindholm, & Marttinen, ). However, these endocytosis inhibitors could not be used for improving rhBMP‐4 production because they impaired cell growth and viability (data not shown).…”
Section: Discussionsupporting
confidence: 93%
“…The association of dynamin with the clathrin‐dependent pathway is well known, though some evidence also implicates its association with the caveolin‐dependent pathway (Doherty & McMahon, ). These results are consistent with the previous studies showing that chlorpromazine and dynasore reduced rhBMP‐2 internalization (Alborzinia et al, ; Jortikka, Laitinen, Lindholm, & Marttinen, ). However, these endocytosis inhibitors could not be used for improving rhBMP‐4 production because they impaired cell growth and viability (data not shown).…”
Section: Discussionsupporting
confidence: 93%
“…4 H-L). We propose that total Gbb levels are not reduced as dramatically as neuronal Gbb-HA because the presynaptic terminal also likely contains internalized muscle-derived Gbb by virtue of trans-synaptic pro-growth signaling (Alborzinia et al, 2013; Kelley et al, 2009; von Einem et al, 2011). We next asked whether Gbb levels in presynaptic terminals decrease following stimulation in the absence of Cmpy.…”
Section: Resultsmentioning
confidence: 94%
“…S1). While Gbb in the presynaptic compartment may be neuron-derived, it may also represent muscle-derived ligand, as Gbb is present in internalized endosomes (Alborzinia et al, 2013; Kelley et al, 2009; von Einem et al, 2011). To test if at least some presynaptic Gbb arises within the presynaptic neuron, we asked whether presynaptic Gbb levels are increased following neuronal Gbb overexpression.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study had demonstrated that BMP‐2 is localized to the late endosomal vesicles through a specific receptor that might be involved in autophagosome biogenesis. Besides, it is documented that hVps34 is essential for the formation of internal vesicles within multivesicular bodies .…”
Section: Resultsmentioning
confidence: 99%